Do Optic Nerve Head and Visual Field Parameters in Patients with Obstructive Sleep Apnea Syndrome Differ from those in Control Individuals? - Salzgeber, R.; Iliev, M. E.; Mathis, J. (Klinische Monatsblätter für Augenheilkunde, 2014)
Background: It has been suggested that sleep apnea syndrome may play a role in normal-tension glaucoma contributing to optic nerve damage. The purpose of this study was to evaluate if optic nerve and visual field parameters in individuals with sleep apnea syndrome differ from those in controls. Patients and Methods: From the records of the sleep laboratory at the University Hospital in Bern, Switzerland, we recruited consecutive patients with severe sleep apnea syndrome proven by polysomnography, apnea-hypopnea index > 20, as well as no sleep apnea controls with apnea-hypopnea index < 10. Participants had to be unknown to the ophtalmology department and had to have no recent eye examination in the medical history. All participants underwent a comprehensive eye examination, scanning laser polarimetry (GDx VCC, Carl Zeiss Meditec, Dublin, California), scanning laser ophthalmoscopy (Heidelberg Retina Tomograph II, HRT II), and automated perimetry (Octopus 101 Programm G2, Haag-Streit Diagnostics, Koeniz, Switzerland). Mean values of the parameters of the two groups were compared by t-test. Results: The sleep apnea group consisted of 69 eyes of 35 patients; age 52.7 ± 9.7 years, apnea-hypopnea index 46.1 ± 24.8. As controls served 38 eyes of 19 patients; age 45.8 ± 11.2 years, apnea-hypopnea index 4.8 ± 1.9. A difference was found in mean intraocular pressure, although in a fully overlapping range, sleep apnea group: 15.2 ± 3.1, range 8–22 mmHg, controls: 13.6 ± 2.3, range 9–18 mmHg; p < 0.01. None of the extended visual field, optic nerve head (HRT) and retinal nerve fiber layer (GDx VCC) parameters showed a significant difference between the groups. Conclusion: Visual field, optic nerve head, and retinal nerve fiber layer parameters in patients with sleep apnea did not differ from those in the control group. Our results do not support a pathogenic relationship between sleep apnea syndrome and glaucoma.
Keywords: sleep apnea; normal- tension glaucoma; RNFL thickness; nerve fiber layer; optic nerve head; visual field